Mulheres na imprensa: representações femininas no Correio Oficial, Cidade de Goiás (1930-1936) - Diniz, Sávia Barros (2013)
This work presents an historical research on the representations of women in the chroniques and articles from a Brazilian newspaper (City of Goiás), Correio de Goiás, in the period 1930-1936. Despite its name, this newspaper was a mixture of official documents, political and social news and opinions columns. This discourses had been generated in political and social transition context from the Belle Epoche, the crisis of the decade of 1920, the advent of the Revolution of 1930 and the Estado Novo of Getúlio Vargas. This context had been marked by social, political and economic changes but at same time by permanences in the Brazilian society. The newspaper texts had been written by doctors, religious men, teachers, civil servants and intellectuals and had been analysed through the historical category of gender relations. This research focuses on the representations of women, which had been built and spread through those newspaper discourses. Such representations in the press had sought to establish the boundaries of social roles of men and women in the City of Goiás. The vilaboenses women had to face and choose between tradition and transgression or in their private daily life (marriage, divorce, attitides, fashion, consumption etc.) or in their urban life (work, sociability, education, culture, citizenship and emancipation)